2020
DOI: 10.1186/s12870-020-02413-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of the combined stresses of freezing-thawing, acid precipitation and deicing salt on alfalfa seedlings

Abstract: Background Frequent freeze-thaw phenomena, together with widely used deicing salt and intense acid precipitation, often occur in northeastern China, causing damage to various aspects of plants, such as the permeability of biological membranes, osmotic adjustment, and photosystems. Aiming to explore the resistance of alfalfa to freezing-thawing (F), acid precipitation (A) and deicing salt (D), this study used Medicago sativa cv. Dongmu-70 as the experimental material, and the contents of malondialdehyde (MDA), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…Previous studies have shown that SAR can induce soil and water acidification, forest decline, and damage to buildings, resulting in heavy economic losses to local governments [ 9 , 10 ]. Furthermore, SAR has complex ecological consequences in plants, such as stunting their height, degrading root system growth, interrupting the accumulation of low-molecular-weight solutes, and obstructing the transportation of nutrients, which can adversely influence biomass accumulation, decrease plant resistance to unfavorable conditions, and induce mortality [ 11 , 12 , 13 ]. Therefore, physical, chemical, and/or biological approaches applied to remediate the detrimental effects of SAR or improve resistance to SAR have received increased attention [ 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SAR can induce soil and water acidification, forest decline, and damage to buildings, resulting in heavy economic losses to local governments [ 9 , 10 ]. Furthermore, SAR has complex ecological consequences in plants, such as stunting their height, degrading root system growth, interrupting the accumulation of low-molecular-weight solutes, and obstructing the transportation of nutrients, which can adversely influence biomass accumulation, decrease plant resistance to unfavorable conditions, and induce mortality [ 11 , 12 , 13 ]. Therefore, physical, chemical, and/or biological approaches applied to remediate the detrimental effects of SAR or improve resistance to SAR have received increased attention [ 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MDA content is a reflection of lipid peroxidation and is usually used to measure stress-induced damage at the cellular level [ 27 ]. In this study, Kobresia pygmaea in different months showed responses to temperature changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the changes in MDA content of the two grass species were different. O2-belongs to oxygen-containing free radicals, and when plants are exposed to external stimuli, they will cause the accumulation of O2-in cells [71,72]. This may be because, for plants, too strong or weak light has a stress effect on the plants, which increases the amount of active oxygen in the plant, and reduces the activity of the antioxidant enzyme system, which is caused by the inability to clean up the excess active oxygen in time [73].…”
Section: Discussionmentioning
confidence: 99%